Design Innovation and Entrepreneurship Organization Based on Psychological Cognitiveness of the Space Narrative - Hu, Jieming; Zhang, Xin (Frontiers in Psychology, 2022)
The high-quality workspace can be used as a physical carrier for design innovation and entrepreneurial organizational culture to continuously change the psychological cognition and behavior of employees in community of practice. The spatial narrative of the culture of design innovation and entrepreneurial organizations means to integrate entrepreneurship and organizational culture into the space through visual presentation. Whether the spatial narrative is successful or not needs to be judged by whether the change of people's psychological cognition achieves the expected effect. The traditional qualitative research methods such as interviews and questionnaires cannot fully and accurately present the psychological cognitive mechanism of design Innovation and entrepreneurship organization members. We use virtual reality technology combined with electrophysiological technology to conduct experiments. We use these technologies to conduct quantitative experiments on psychological cognition in community of practice. This study will select a design innovation and entrepreneurial organization , randomly select 20 participants, and divide them into 2 groups for experimentation. The VR scene is based on their real office space as a prototype. Put the visual elements of corporate culture in one of the VR scenes. The other VR scene as a reference does not incorporate visual elements of organizational culture.Participants participated in the experiment in these two VR scenarios.There are many advanced devices that can accurately test individual psychological changes, but the ErgoLab man-machine environment test platform,can collect and compare these data (physiological data, EEG data and behavior data) in real-time and comprehensively, which is its advantage. According to the experimental results, judge the changes in the psychological cognitive data of the participants before and after the placement of the spatial narrative in design innovation and entrepreneurial organizations. The experiment combined interviews and questionnaires to ensure the authenticity of the quantitative data. The conclusion of the experiment will produce an accurate quantitative study on the psychological cognition of the spatial narrative of design innovation and entrepreneurial organizational culture.A sense of organizational belonging,collective sense,pride, mission and work fun can be generated in the workspace.